2016
DOI: 10.1134/s0006297916120087
|View full text |Cite
|
Sign up to set email alerts
|

Effect of alpha-fetoprotein on lifespan of old mice

Abstract: Alpha-fetoprotein (AFP) is one of the best-known embryo-specific proteins. It is used to diagnose fetal abnormalities and tumors of the gastrointestinal tract and liver. AFP has pronounced immunotropic and detoxifying effect and a direct apoptotic effect on tumor cells. The treatment of mice at the oldest age in our experiments with AFP dramatically increased the survival and markedly increased the relative weight of immunotropic organs, apparently due to the general effect of AFP in improving functions of tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…However, animal trials have shown a characteristic effect of several popular pharmacological agents, demonstrating an increase in longevity, i.e. the inhibition of aging or "geroprotective effect" (5,11,12,19,21). This effect is shown, in particular, for aspirin (51,52), metformin (53), rapamycin (54), and some other drugs (11,12,19).…”
Section: Geroprotectors As a Natural Part Of The Pharmacopeiamentioning
confidence: 99%
See 2 more Smart Citations
“…However, animal trials have shown a characteristic effect of several popular pharmacological agents, demonstrating an increase in longevity, i.e. the inhibition of aging or "geroprotective effect" (5,11,12,19,21). This effect is shown, in particular, for aspirin (51,52), metformin (53), rapamycin (54), and some other drugs (11,12,19).…”
Section: Geroprotectors As a Natural Part Of The Pharmacopeiamentioning
confidence: 99%
“…together with reduced working capacity, adaptation ability, physical strength, and intellectual capacity. Moreover, to date a significant amount of experimental data on "anti-aging drugs" (or "geroprotectors") has accumulated (6,(11)(12)(19)(20)(21). A new field of practical medicine, so-called "anti-aging medicine", is rapidly developing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the function of T-lymphocytes is suggested decrease sharply during aging due to changes in the organism's regulatory systems. We have discovered a variety of experimental evidence and have shown that it is possible to reactivate and rapidly regenerate the growth potential of somatic cells under the influence of the imminity [31,32].Thus, the proposed new immune-age theory is not only of theoretical interest but also makes it possible to use the whole potential of immunopharmacology to counteract one of the crucial mechanisms of aging: the age-related decrease in cell selfrenewal in the multicellular organisms, including mammals and humans.…”
Section: Vmentioning
confidence: 99%
“…We have discovered a variety of experimental evidence and have shown that it is possible to reactivate and rapidly regenerate the growth potential of somatic cells under the influence of the immunity and to reverse the symptoms of aging in the experiment [32,33]. Thus, the proposed new immune-age theory is not only of theoretical interest but also makes it possible to use the whole potential of immuno-pharmacology to counteract one of the crucial mechanisms of aging: the age-related decrease in cell self-renewal in the multi-cellular organisms, including mammals and humans.…”
Section: F)mentioning
confidence: 99%